2013
DOI: 10.1158/1535-7163.mct-12-1079
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibitor BMS-777607 Induces Breast Cancer Cell Polyploidy with Increased Resistance to Cytotoxic Chemotherapy Agents

Abstract: The RON receptor tyrosine kinase is a therapeutic target for cancer treatment. Here, we report therapeutic effect and phenotypic change of breast cancer cells in response to BMS-777607, a RON tyrosine kinase inhibitor. Treatment of breast cancer cells with BMS-777607 at therapeutic doses inhibited cancerous clonogenic growth but had only minimal effect on cell apoptosis. Significantly, BMS-777607 induced extensive polyploidy with multiple sets of chromosomes in cancer cells. This effect is independent of RON e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 34 publications
0
59
0
Order By: Relevance
“…Nuclear DNAs were stained with 4 0 ,6-diamidino-2-phenylindole (DAPI). Immunofluorescence was observed under an Olympus BK71 microscope equipped with DUS/fluorescent apparatus as previously described (30). …”
Section: Detection Of Internalized Ronmentioning
confidence: 99%
“…Nuclear DNAs were stained with 4 0 ,6-diamidino-2-phenylindole (DAPI). Immunofluorescence was observed under an Olympus BK71 microscope equipped with DUS/fluorescent apparatus as previously described (30). …”
Section: Detection Of Internalized Ronmentioning
confidence: 99%
“…Studies from tumor xenograft models have shown that BMS-777607 at 6.25 mg/kg (C max ¼ 4.5 mmol/L) has a therapeutic effect, which significantly inhibits tumor growth mediated by gastric GTL-16 cancer cells that overexpress MET (16). We have recently observed that BMS-777607 inhibits clonogenic growth and induces apoptosis in breast cancer cells exclusively expressing RON (17). Moreover, BMS-777607 induces extensive polyploidy in breast cancer cells at therapeutic doses by inhibition of aurora kinase B (AUKB; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, BMS-777607 induces extensive polyploidy in breast cancer cells at therapeutic doses by inhibition of aurora kinase B (AUKB; ref. 17). In this sense, BMS-777607 can be considered as a multi-TKI (16,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these receptors, the Ron receptor tyrosine kinase, has been implicated as an oncogene in numerous reports [3-7], and is emerging as a cancer therapeutic target [6]. While the use of selective inhibitors and monoclonal antibodies against Ron have shown promise in vitro and in vivo inhibiting tumor growth, potential side effects and lack of complete inhibition [6, 8, 9] call for the development of new therapeutic approaches. Hepatocyte growth factor-like protein, HGFL, is the ligand for Ron receptor tyrosine kinase.…”
Section: Introductionmentioning
confidence: 99%